RELATIONSHIP OF SPIRITUALITY AND RELIGIOUS PRACTICES FOR SUSTAINABLE DEVELOPMENT OF HUMAN BEINGS - Tirtha Raj Ghimire (International Engineering Journal For Research & Development, 2024)
This research aims to highlight the importance of spirituality and religion in promoting human survival and development, as well as their influence on the environment. It emphasizes the interconnectedness of spirituality and religion with human consciousness, and how understanding these concepts forms the basis of human survival. The study uses data from various religious texts, YouTube programs, and individual perspectives to examine the impact of spirituality and religion on human survival. It finds that neglecting spirituality and religion can lead to self-destruction. Spiritual and religious practices also contribute to human survival by promoting awareness of nature and judicious use of natural resources, especially in the era of globalization driven by economic forces. The study's scope is limited to spirituality and religion for sustainable human development, but its practical significance lies in raising public awareness about the role of spirituality and religion in ensuring human existence and maintaining its originality.